Pengaruh Literasi Keuangan, Gaya Hidup, Kontrol Diri, dan Sikap Keuangan terhadap Pengelolaan Keuangan FEB UNESA - Abid Rabbulizat Rajendra Ekofani; R.A. Sista Paramita (ARBITRASE: Journal of Economics and Accounting, 2023)
This study aims to identify the influence of financial literacy, lifestyle, self-control, and financial attitudes on the financial management of active students in the Faculty of Economics and Business at Surabaya State University. This is a quantitative research study, and the data used are primary data. The sampling method used is purposive sampling. The population of this study is all active students in the Faculty of Economics and Business at Surabaya State University for the academic year 2022-2023, totaling 4,401 students. The total sample size used is 110 students. The analysis method used is multiple linear regression. The result show that financial literacy has a positive and significant influence on students' financial management. Lifestyle does not have an influence on students' financial management. Self-control has a positive and significant influence on students' financial management. Financial attitudes do not have an influence on students' financial management. The coefficient of determination is 0.456 or 45.6 percent, indicating that financial literacy, lifestyle, self-control, and financial attitudes account for 45.6 percent of the variation in financial management, while he remaining 54.4 percent is influenced by other variables such as parental income, family environment, and financial education within the family, which are not included in this study.